Pengaruh Kebijakan Dividen Dan Kinerja Keuangan Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesiatahun 2015-2017 - Lasria Sinaga; Jihen Ginting (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2020)
Abstract : The problem in this research is dividend policy and financial performance affect the value of the company. When the financial performance of a company is weak, then the company can go bankrupt and ultimately will have no value. The purpose of this study was to determine the effect of dividend policy and financial performance on the value of companies in manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The population of this research is 143 companies listed on the Indonesia Stock Exchange in 2015-2017. The research sample was 40 companies with purposive sampling method, with quantitative research types. The data used is secondary data, namely the company's financial statements obtained from www.idx.co.id., https://finance.yahoo.com, or from the company's official website. The independent variable used is dividend policy that is proxied by dividend payout ratio (DPR) and financial performance that is proxied by return on net operating assets (RNOA). The dependent variable is the value of the company that is proxied by price book value (PBV). This research uses multiple linear regression analysis techniques using the SPSS statistical test tool. Based on the results of this research partially and simultaneously showed that the dividend policy variables and financial performance significantly influence the value of the company. This is evidenced by the significance value of the partial dividend policy (T Test) of 0,000 or less than 0.05. The significance value of the financial performance partially (T Test) is 0,000 or less than 0.05. Then the simultaneous significance value (Test F) is 0,000 which is below 0.05. The conclusion of this research is that dividend policy and financial performance partially or simultaneously influence the value of the company. This means that these factors can influence the value of the company in manufacturing companies listed on the Indonesia Stock Exchange.Keyword : Company Value, Dividend Policy, Financial Performance